Phase Composition of Ni/Mg1−xNixO as a Catalyst Prepared for Selective Methanation of CO in H2-Rich Gas. (10th February 2015) - Zhang, Mengmeng; Ma, Hongwei; Gao, Zhiming
Abstract : Supported Ni catalysts Ni/Mg1− x Ni x O were prepared by reducing samples NiO-MgO in H2 /N2 mixture gas at 500°C~800°C for selective methanation of CO in H2 -rich gas (CO-SMET). The samples NiO-MgO were obtained by heating water slurry of MgO and Ni(NO3 )2 in a rotary evaporator at 80°C and a final calcination in air at 400°C~800°C. X-ray diffraction (XRD) and temperature programmed reduction (TPR) measurements demonstrate that the samples NiO-MgO were composed of solid solution Mg1− y Ni y O as the main phase and a minor amount of NiO at calcination temperature of 400°C, and amount of the NiO was decreased as calcination temperature increased. Phase composition of the catalysts Ni/Mg1− x Ni x O was estimated by the Rietveld method. Effects of reduction temperature, feed Ni/Mg ratio, and calcination temperature on phase composition and catalytic activity of the catalysts were investigated. It is clear that CO conversion was generally enhanced by an increased amount of metallic Ni of the catalysts.